Acoustic performance of embedded gypsum panels with cellulose fibers - Araujo, Sâmique Kyene de Carvalho; Oliveira, Diego Rodrigues de; Silva, Tiago José da; Barbosa, Juliana Cortez; Gava, Maristela (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
Currently, with the rationalization of consumption of raw materials due to energy constraints and possible damage to the environment , it has tried to maximize their employability . The forestry - wood sector is largely responsible for the generation of waste , which must be allocated appropriately to not lead to environmental damage. Thus, this study aimed to evaluate the acoustical panels made of plaster embedded with cellulose fibers from a pulp and paper company of the Paulista West . The evaluation was made based on the sound absorption material, resulting in sound absorption coefficients at around X, according to values found in literature.